Experimental study on gasification mechanism of unburned pulverized coal catalyzed by alkali metal vapor. Issue 2 (April 2020) - Ning, Xiaojun; Peng, Zhengfu; Wang, Guangwei; Zhang, Jianliang; Song, Tengfei
Abstract: The catalytic behavior of alkali vapor on unburned pulverized coal (UPC) prepared from bituminous coal, anthracite, semi coke and coke have been investigated. Experiment results show that the alkali metal vapor has catalytic effect on the gasification reaction of UPC. The catalytic effect of coke UPC is the most obvious, followed by anthracite UPC and bituminous coal UPC. Semi coke UPC is the least catalyzed by alkali metals but its gasification reactivity is the best. As the concentration of alkali metal vapor increases, the alkali metal content adsorbed by UPC increases, and there may be a phenomenon of saturated adsorption. The amount of alkali metal adsorbed is between 2% and 6%. AUPC has the highest ability to adsorb alkali metals, and SUPC is the weakest, which may be related to the minerals (CaO, Al2 O3 ) in the coal ash. Changes in stomatal parameters are not the main factors affecting the catalytic effect. The results of X-ray diffraction experiments show that alkali metal aluminosilicate exists in the ash of coal after adsorption of alkali metal, and the average stack height of carbon atoms decreases significantly. The alkali metal catalytic gasification reaction is mainly achieved by destroying the carbon basic structural unit. The alkali metal nepheline and the interlayer compound may be the main catalytic substances, and the destructive ability of alkali intercalation is obviously stronger than that of alkali nepheline. The catalytic mechanism of alkali metals on unburned coal and the destruction mechanism of alkali metals on carbon crystals were discussed. It can provide reference for reducing alkali metal corrosion on coke and improving pulverized coal utilization rate. Highlights: The behavior of alkali metals in the form of vapors interacting with unburned coal powder was investigated. The variation of CO2 gasification reaction of carbon by different alkali metal vapor concentrations was studied. The ability of unburned coal and coke to adsorb alkali metals at different alkali metal concentrations was investigated. Analysis of the mechanism of alkali metal catalyzed CO2 gasification by oxygen transfer theory.